PENGARUH PENGAWASAN PREVENTIF, PENGAWASAN DETEKTIF DAN PENGANGGARAN BERBASIS KINERJA TERHADAP EFEKTIFITAS PENGENDALIAN ANGGARAN. (STUDI EMPIRIS PADA SKPD KOTA DUMAI) - Baskara, Bayu Yosa; Nasir, Azwir; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the Effects of Preventive Monitoring, Detective Monitoring, and Performance-Based Budgeting on Effectiveness Budgetary Control survey on the Lokal Government Unit (SKPD) district at Dumai of Riau Province as the research object. The population used in this study was 33 on the Lokal Government Unit (SKPD) at Dumai city of Riau Province. Sample in this research used the purposive sampling. The sample is head of department, head of division/secretary, and head of subsection. The amount of respondent in this research was 99, only 87 copy questonnaires can be proccessed This type of data is the primary data with collection method with questionnaires. The analysis data techniques using Structural Equation Model (SEM) with the help smartPLS ver. 3.0 was used to test whethe independent variables affect to dependent variables.The result of this study indicate that the variable of preventive monitoring, detective monitoring and Performance-Based Budgeting is influence the efectiveness budgetary control. The result also showed the contribution of preventive monitoring, detective monitoring, and performance-based budgeting on effectiveness Budgetary Control is equal 82,4%. While the remaining 17,6% is influenced by other variables not included in this smartPLS model.Keywords : Effect of Preventive Monitoring, Detective Monitoring, Performance Based Budgeting and Effectiveness Budgetary Control